2021
DOI: 10.1111/mmi.14842
|View full text |Cite
|
Sign up to set email alerts
|

KH domain proteins: Another family of bacterial RNA matchmakers?

Abstract: In many bacteria, the stabilities and functions of small regulatory RNAs (sRNAs) that act by base pairing with target RNAs most often are dependent on Hfq or ProQ/FinO‐domain proteins, two classes of RNA chaperone proteins. However, while all bacteria appear to have sRNAs, many have neither Hfq nor ProQ/FinO‐domain proteins raising the question of whether another factor might act as an sRNA chaperone in these organisms. Several recent studies have reported that KH domain proteins, such as KhpA and KhpB, bind s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…Interestingly, we also observed that the putative RBPs KhpA and KhpB (Olejniczak et al, 2021) showed strong tailing towards the RNAP and 30S fractions (Fig. 5A).…”
Section: The Emerging Rna-binding Protein Khpb Is Conserved In Entero...mentioning
confidence: 59%
“…Interestingly, we also observed that the putative RBPs KhpA and KhpB (Olejniczak et al, 2021) showed strong tailing towards the RNAP and 30S fractions (Fig. 5A).…”
Section: The Emerging Rna-binding Protein Khpb Is Conserved In Entero...mentioning
confidence: 59%
“…Previous results and those reported here show that Δ pbp1a suppresses the requirement for MreC, MreD, and RodZ (Table 1) (Fenton et al ., 2016, Land & Winkler, 2011, Tsui et al ., 2016). Likewise, Δ khpA and Δ khpB mutations, which result in the absence of the major KhpAB RNA-binding regulatory protein (Hor et al ., 2020, Olejniczak et al ., 2022), suppress Δ mreCD and Δ rodZ mutations (Table 1) (Zheng et al ., 2017). These results are reiterated by Tn-seq analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structures studied here may also provide a clue as to the mechanism for other effector complexes known to engage RNase E. For instance, the regulatory protein CsrD, which is required for specific turnover of the sRNAs CsrB and CsrC by RNase E (Vakulskas et al, 2016;Potts et al, 2018), may present those RNAs for structure-based recognition in analogy to the RapZ/GlmZ complex studied here. A similar scenario could also apply to recently identified RNA-binding proteins in non-model bacteria such as CcaF1, which modulates degradation of selected transcripts by RNase E in Rhodobacter sphaeroides (Grützner et al, 2021), or to the emerging class of KH proteins that may act as sRNA chaperones in Gram-positive bacteria (Olejniczak et al, 2021). It can even be envisaged that the global RNA chaperone Hfq may form encounter complexes analogous to RapZ to facilitate degradation of base-paired sRNA/target RNAs by RNase E (Figure 5a, right panel).…”
Section: Discussionmentioning
confidence: 95%